PWE-354 Can we safely carry out less intensive colonoscopy surveillance in patients post curative colorectal cancer resection?. (22nd June 2015) - Johnston, EL; Zacks, A; Shaheen, S; Ataklte, F; George, M; Dunn, JM
Abstract : Introduction: London Cancer Alliance (LCA) published their guidelines on colorectal cancer (CRC) in September 2014. 1 They highlight that intensive colonoscopic follow up does not have a significant effect on survival. As a result the guidelines recommend a less rigorous regimen than we currently adopt; a full colonoscopy at 1 year and then 5 years post operatively if a complete procedure was done at diagnosis and no abnormalities are detected during surveillance. The aim of this study is to retrospectively determine whether any recurrence or new cancers would have been missed should the guidelines have been implemented. Method: An endoscopy database search of patients who underwent a colonoscopy for CRC surveillance from 1 st January 2008 to 31 st December 2013 was carried out. The follow up interval of the cohort diagnosed and treated in 2007 was then assessed for 5 years using clinical records. Results: During the 6-year period 495 colonoscopies were carried out for CRC surveillance. From these, 49 patients were identified who had been diagnosed and treated in 2007. Six patients had polyps found during surveillance and followed up according to the British Society of Gastroenterology (BSG) polyp guidelines, 2 so were removed from analysis. Of the remaining 43 patients, 27 (62.8%) were discharged after 5 years of follow up, 12 (27.9%) died and 4 (9.3%) remain under follow up due to recurrent disease diagnosed either on radiological imaging or during colonoscopy. Over a 5-year time period 71 colonoscopies were carried out on 31 patients, averaging at 2.3 colonoscopies per patient. 15 patients had 3 or more colonoscopies in the study period. Recurrence was only seen on 2 colonoscopies, 1 year post surgery in one patient and 5 years post surgery in the other, both of which would have been identified if the new LCA guidelines were adopted. Conclusion: In this retrospective study, adoption of the LCA guidelines for CRC surveillance post curative surgery does not increase the miss rate for recurrence. In addition, 15 patients (48.4%) would have had fewer unnecessary colonoscopies, reducing risk to the patient and cost. A prospective study is warranted. Disclosure of interest: None Declared. References: LCA Colorectal Cancer Clinical Guidelines. September 2014. http://www.londoncanceralliance.nhs.uk/media/83350/lca_colorectalclinicalguidelines2014.pdf Cairns S, Scholefield J, Steele R, et al . Guidelines for colorectal cancer screening and surveillance in moderate and high risk groups (update from 2002). Gut. 2010;59:666–690